Xiphonectes aculeatus sp. nov., a new swimming crab (Crustacea: Decapoda: Portunidae) from Madagascar - Koch, Milan; Ďuriš, Zdeněk (Zootaxa, 2019)
Here we describe a new species of Xiphonectes A. Milne-Edwards, 1873 (Brachyura: Portunidae) from southern Madagascar. Xiphonectes aculeatus sp. nov. is morphologically most similar to X. latibrachium (Rathbun, 1906) from Hawaii, and X. paralatibrachium Crosnier, 2002, from the Marquesas Islands, French Polynesia. All three species have a carapace with six anterolateral teeth, a long spine on the inner dorsal margin of the cheliped carpus, and a produced, flattened, anterior region on the third maxilliped merus. Among these species, Xiphonectes aculeatus sp. nov. is easily distinguished by the acutely produced posterodistal angle on the meri of its swimming legs, dorsal and marginal structures on its carapace, and most notably, the shape of its frontal teeth.